Spatio-temporal fusion of NDVI data for simulating soil water content in heterogeneous Mediterranean areas. Issue 1 (1st January 2019) - Chiesi, Marta; Battista, Piero; Fibbi, Luca; Gardin, Lorenzo; Pieri, Maurizio; Rapi, Bernardo; Romani, Maurizio; Sabatini, Francesco; Maselli, Fabio
ABSTRACT: Recent studies have demonstrated that the soil water content (SWC) of Mediterranean ecosystems can be simulated by combining ground data and remote sensing observations of Normalized Difference Vegetation Index (NDVI). The application of this approach in heterogeneous and fragmented areas, however, requires the use of spatio-temporal fusion (STF) methods to properly account for the actual NDVI variability of the examined ecosystems. One of these methods, which was specifically developed to produce annual NDVI data series in Mediterranean regions, is currently applied to MODIS and TM/ETM+ images taken over a highly fragmented green urban area in Florence (Central Italy). The performances of this STF method, called SEVIS, are indirectly evaluated by comparing local SWC measurements to simulations driven by the original (MODIS) and fused (MODIS+TM/ETM+) NDVI datasets. The results obtained confirm the critical dependence of the applied SWC simulation strategy on the efficient accounting for the actual NDVI evolution of the observed ecosystem. In particular, the use of the fused NDVI dataset corrects almost completely for the strong SWC underestimation produced by the original MODIS images during the summer dry period, significantly improving all accuracy statistics ( r 2 from 0.564 to 0.855, RMSE from 0.101 to 0.044 cm 3  cm −3 and MBE from −0.046 to 0.000 cm 3  cm −3 ).